Ecological Consumer Profile in Companies in Pachuca, Hidalgo - Cerón Islas, Arlén; Alarcón Ruvalcaba, María José (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
The growing concern for the environment in Mexico has had a notable increase, resulting in a great opportunity for companies that opt for this alternative; however, despite this general interest, there has been less success in certain areas of the population such as Pachuca, Hidalgo. OBJECTIVE: To analyze the factors that influence the purchase decision of ecological products in consumers. MATERIAL AND METHOD: A quantitative research was carried out, with a sample of 164 participants in a 14-item survey. RESULTS: There are very few sales points and a scarcity of this type of product, the purchase is influenced by reference groups and the traits to be considered are biodegradable packaging, certified labels, price, and trust in quality; the most consumed products are those of hygiene and beauty. CONCLUSIONS: There is a great paradox consisting of the low level of consumption of ecological products and the care of the environment; giving rise to three consumer profiles - the imitator, the Eco Lifestyle, and the involved.